Gamification in Marketing: Analyses of the Impact Beyond Play and Fun (European Journal of Behavioral Sciences, 2025)
As marketers increasingly face the challenge of capturing and maintaining consumer attention in a saturated digital environment, gamification has emerged as a promising solution. Gamification has emerged as a transformative strategy in marketing, extending its influence far beyond play and entertainment. This conceptual paper employs a meta-analysis methodology, systematically synthesizing findings from academic, experimental, and applied research to uncover consistent patterns, theoretical developments, and evolving applications of gamification in marketing contexts. The choice of meta-analysis is particularly relevant as it allows for the integration of diverse empirical and conceptual studies, offering a comprehensive and evidence-based understanding of the field’s development over time. In addressing the first research question, the study explores how gamification has been conceptualized and applied, highlighting key elements such as points, leaderboards, challenges, and rewards, and examining their effects on consumer engagement, loyalty, and behavior through psychological mechanisms like intrinsic and extrinsic motivation. The second research question identifies existing gaps in literature, including the need for longitudinal research, greater cultural diversity, and ethical scrutiny in the deployment of gamified systems. By integrating theoretical frameworks such as Self-Determination Theory, Flow Theory, and the Technology Acceptance Model, the paper not only clarifies how gamification works but also guides future research toward more responsible, inclusive, and effective applications. The findings offer valuable insights for scholars and marketing practitioners seeking to design gamified strategies that are not only engaging but also sustainable and ethically sound.